Research advances on mist assisted impingement and film cooling of turbine blades - Biswal, Pratibha; P., Mallikarjuna Rao; Balaji, C. (International journal of heat and mass transfer, 2024)
Impingement and film cooling techniques are emerging areas in the turbine component cooling technology. Vast amount of information on this subject is available in the literature and mist assisted turbine blade cooling has been attempted by many researchers since last decade. This article presents a comprehensive review focusing on the mist assisted impingement and film cooling of turbine blades. Common to all the mist assisted works, the addition of water mist with the regular air/steam coolant is beneficial for the cooling phenomena which was observed from the lower surface temperature for the mist cases. Larger mist concentration in the coolant mixture and smaller droplets are advantageous as that results in higher evaporation and better cooling. Better cooling performance is observed with uniform droplet size distribution compared to that for the non-uniform droplet size distribution. During mist assisted impingement cooling, the effects of parameters such as mist loading fraction (f), droplet diameter (dp), geometry of the impinging surface, Reynolds number (Rep), heat flux on the surface, number of holes, number of rows of holes, confinement (nozzle to plate ratio) working conditions (elevated and laboratory) etc. on the cooling performance are discussed in detail. Similarly, comprehensive analysis of effects of mist characteristics (mist concentration, droplet diameter, mist temperature), coolant characteristics (blowing ratio, temperature, relative humidity), geometrical characteristics (curved, flat, ribbed surfaces, presence of deposition) etc. on the film cooling performance are featured in this article. Information of this review will be useful as a reference for researchers and engineers interested in working with energy efficient gas turbine component cooling technology. •Mist-assisted impingement and film cooling methods are reviewed.•Inclusion of mist in coolant boosts cooling performance.•Ensuring even mist distribution and combating corrosion are major challenges.•Research needed for engine conditions-like temperature, pressure and geometric conditions.•Exploration of additive manufacturing and data-based optimization is required.